Maintaining Sustainability of Tourism Kampong. The Case of Kampong Pelangi in Semarang - SARI, Suzanna Ratih; HENDRO, Eko Punto; HILMY, Muhammad Fariz (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
In the beginning, Kampong Pelangi in Semarang was a slum area, then it creatively changed as an interesting tourist attraction. The community of tourism awareness called pokdarwis has formed to manage tourism activities in the village. Nonetheless, pokdarwis, which should have an important role in the development of tourism, in fact, it is getting fainter. Even today, it can be said that pokdarwis role is no longer significant as each community has initiated to carry out tourism activities and promote Kampong Pelangi tourism independently, in which the impact of tourism is no longer felt by the community as a whole but rather the individual community itself. Based on the above phenomenon, this study was conducted to identify obstacles experienced by pokdarwis in maintaining the sustainability of tourism in Kampong Pelangi. Using qualitative methods, the research outcome will be a tourism development strategy related to strengthening the role of pokdarwis in Kampong Pelangi.